KIM VOCABULARY BUILDING STRATEGY: IMPLEMENTATION AND IMPLICATIONS FOR VOCABULARY TEACHING - Erniwati, Erniwati; Arid, Muhammad; Maghfira, Maghfira; Manurung, Grace Novenasari (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
The focus of teaching English at schools, especially for beginners is to build vocabulary knowledge in addition to language skills and components. To achieve the goal, KIM Strategy can be implemented, which becomes the topic of this paper. Hence, this paper aims to review the related literature on the implementation and implication of KIM Strategy for vocabulary teaching. This is a library research, in which two types of data were presented. They were  primary and secondary data. The primary data was obtained from the original work of Kristen Vibas (1970), the proponent of the KIM Strategy, entitled KIM: A highly effective strategy to build vocabulary across any content area. Whilst, the secondary data were collected from journal articles published in the past 10 years, 2014-2024. The results revealed that the KIM Strategy is effective in improving students’ vocabulary knowledge due to its teaching principles that support various principles of inquiry learning, self-directed learning, and social learning. The KIM Strategy is also a strategy for enhancing logical, convergent, and divergent thinking skills.